Pengaruh Work Environment dan Quality of Work Life terhadap Employee Performance Generasi Z dengan Mental Health sebagai Variabel Mediasi - Mikael Hendri. S; Ramadania Ramadania; Ikram Yakin; Hasanudin Hasanudin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of work environment and quality of work life on employee performance, with mental health as a mediating variable among Generation Z employees in startup companies across Indonesia. The population in this research consists of Generation Z individuals working in startups throughout the country. The study employs the Structural Equation Modeling (SEM) method to analyze the data. It investigates the significant relationships between work environment, quality of work life, employee performance, and mental health by developing a new model to illustrate the interactions among these variables. The results indicate that improvements in work environment and quality of work life can enhance the performance of Generation Z employees, especially when their mental health is well-maintained. This research contributes to a deeper understanding of the factors influencing employee performance in the context of work environment and quality of work life, and provides recommendations for employees to pay greater attention to their mental health.